Light‐induced electrons suppressed by Eu3+ ions doped in Ca11.94−xSrxAl14O33 caged phosphors for LED and FEDs. Issue 8 (20th April 2017) - Bian, Hongyu; Liu, Yuxue; Yan, Duanting; Zhu, Hancheng; Liu, Chunguang; Xu, Changshan; Wang, Xiaojun; Zhang, Hong
Abstract: Control of light‐induced electron generation is of vital importance for the application of caged phosphors. For Eu‐doped Ca11.94− x Sr x Al14 O33 caged phosphors, the suppressed effect of strontium doping on the light‐induced electrons is observed compared to the europium‐free Ca11.94− x Sr x Al14 O33 phosphors. In the presence of europium ions, Sr doping will promote the reduction of Eu 3+ to Eu 2+ . The Rietveld refinement suggests that unit cell volumes of the Ca11.94− x Sr x Al14 O33 :Eu0.06 samples are expanded when Ca 2+ ions are replaced by Sr 2+ ions. The absorption and FTIR transmittance spectra confirm that the competitive reaction of encaged O 2− anions with H2 is suppressed. For the sample ( x =0.48), the higher thermal activation energy ( 0.40 eV) for luminescence quenching can be attributed to the more rigid framework structure after Sr doping. For Ca11.94− x Sr x Al14 O33 :Eu0.06 phosphors, their emission colours are tuned from red to purple upon 254 nm excitation and from pink to blue under electron beam excitation through Sr substitution. The insight gained from this work may have a significant guiding to design new phosphors for LED and FEDs and novel nanocaged mutifunctional materials.